Pandangan Kiai Nahdlatul Ulama tentang perempuan kandidat pada pemilihan kepala daerah Jawa Timur 2018 - Agustian Putra; Dwi Windyastuti Budi Hendrarti (Universitas Airlangga, 2022)
This research discusses Kiai's views on women candidates in the 2018 East Java regional elections. There are two competing candidates, the Khofifah-Emil and Gus Ipul-Puti pairs. Both Khofifah and Gus Ipul were both from the Nahdliyin circles and claimed to have the support of the Kiai Nahdlatul Ulama. Kiai's support was divided, there were those who supported Gus Ipul and Khofifah. Many fatwa wars and arguments have arisen in the community to strengthen each candidate. One of the arguments that is often conveyed is about gender which looks down on women when going forward as a candidate in the 2018 East Java governor election. There are two competing female candidates namely Khofifah as a candidate for governor and Puti as a candidate for deputy governor. The research method that I used is qualitative-descriptive with observational data collection techniques and in-depth interviews with Kiai both structural Kiai and Nahdlatul Ulama cultural kiai in Surabaya and surrounding areas. The result was that the majority of structural Kiai supported women to run as candidates in the 2018 East Java Governor election. Only a small number of cultural Kiai refused women to run as candidates.